Immune-enhanced effect of Iris polysaccharide is protective against leptospirosis. (May 2021) - Liu, Jiuxi; Xie, Xufeng; Zhang, Wenlong; Cao, Yongguo
Abstract: Leptospirosis, caused by pathogenic Leptospira species, is an essential but neglected zoonosis. There are more than 300 serovars of pathogenic Leptospira, while inactivated bacteria offers only short-term serovar-specific protection. Leptospirosis treatment is mainly dependent on the use of antibiotics. However, the side effects of antibiotics and the risk of antibiotic resistance remain major problems. Thus, alternative agents which are fewer side effects on humans and efficient in leptospirosis would be welcome. Many studies have reported that polysaccharides could be used as immunostimulants in treating infection and cancer. In this study, we examined the protective effect of polysaccharides isolated from Iris against leptospirosis. To our knowledge, it is the first time to report Iris polysaccharides (IP) as an immunostimulant in treating infection. The results showed that IP treatment significantly increased the survival rate of hamsters challenged by a lethal dose of leptospires. Besides, the tissue injury and leptospiral load were reduced in IP-treated infection group compared with the untreated infection group at 4 days post-infection (p.i.). Intriguingly, IP treatment sustained intense immune response at 4 days p.i. analyzed by qPCR. The results exhibited that the gene expression of TLR2 and TLR4 was significantly increased in the group coinjected with IP and leptospires than in the infected controls. And the expression of IL-1β and TNF-α were also up-regulated after IP treatment, except the expression of IL-1β in the kidney. Our results not only broaden the medicinal value of Iris, but also provide a competent candidate for the control of Leptospira infection. Highlights: Iris polysaccharide-treated hamsters showed improved survival rate during Leptospira infection. Iris polysaccharide treatment reduced bacterial load and ameliorated Leptospira-induced organ injury in hamsters. Iris polysaccharide treatment could prolong intense immune response during infection.